Increased Incidence of Rhinovirus Pneumonia in Children During the COVID-19 Pandemic in Mexico - Fanny Yasmin Ortega-Vargas; Aldo Agustin Herrera-González; Ilen Adriana Díaz-Torres; Isamu Daniel Cabrera-Takane; Patricia Bautista-Carbajal; Miguel Leonardo García-León; Daniel E. Noyola; María Susana Juárez-Tobías; Verónica Tabla-Orozco; Pedro Antonio Martínez-Arce; María del Carmen Espinosa-Sotero; Gerardo Martínez-Aguilar; et al. (Advances in Virology)
Conclusions: During the pandemic, a shift toward older age, a higher percentage of coinfections, and increased severity associated to HRV pneumonia were observed. These findings highlight the need for the development and implementation of targeted prevention and treatment measures for HRV.